The Emotional Intelligence Dimensions among Foundation Students - Nurul Hafizah Bongsu; Abu Yazid Abu Bakar (Indonesian Journal of Community and Special Needs Education, 2023)
As a student, intellectual quotient (IQ) is seen as an indicator to measure success. However, to explain the success of one person, psychologists claim that one of the driving factors for an individual's success in whatever they do is the level of emotional quotient (EQ), also known as emotional intelligence. A high level of emotional intelligence has an impact on the ability to manage emotions well, which not only leads to good academic performance but also good social relationships. The purpose of this study was to identify the scale of emotional intelligence dimensions of foundation students to help students to identify and understand the state of their emotional intelligence. There are five dimensions related to emotional intelligence which are; self-awareness, self-control, self-motivation, empathy, and social skills.